The Effect of Trait and State Disgust on Fear of God and Sin - Stewart, Patrick A.; Adams, Thomas G.; Senior, Carl (Frontiers in Psychology, 2020)
There is a growing literature suggesting disgust plays a major role in religiosity. However, the relationships between specific domains of disgust sensitivity and general religious fundamentalism or religious scrupulosity remains unknown and a lack of experimental data prevents the drawing of causal inferences about the potential effects of disgust on religiosity. Two studies are reported that examined the relationship between specific types of disgust sensitivity (i.e., pathogen, sexual, and moral disgust) and specific religious beliefs (i.e., fear of sin and fear of God). In the first study it was found that sexual disgust and pathogen disgust were significantly correlated with fear of sin and fear of God, respectively. In the second study the experimental induction of disgust led to greater fear of sin but not to the fear of God. These findings suggest that pathogen and sexual disgust sensitivities may serve as effective mechanisms for inflated scrupulosity. Taken together the outcomes from both studies converge on a greater understanding of the so called ‘Human Behavioural Immune System’ model that can account for social behaviour with an evolutionary of adaptive benefit and perhaps more importantly highlights the possible drivers of specific religious behaviour.